2018
DOI: 10.1016/j.virusres.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypervariable regions in spike protein on pathogenicity, tropism, and serotypes of infectious bronchitis virus

Abstract: To study the roles of hypervariable regions (HVRs) in receptor-binding subunit S1 of the spike protein, we manipulated the genome of the IBV Beaudette strain using a reverse genetics system to construct seven recombinant strains by separately or simultaneously replacing the three HVRs of the Beaudette strain with the corresponding fragments from a QX-like nephropathogenic isolate ck/CH/LDL/091022 from China. We characterized the growth properties of these recombinant IBVs in Vero cells and embryonated eggs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 60 publications
2
30
2
Order By: Relevance
“…The reduction of the viral load at 5 dpi in the group infected with the rIBYZ strain may be associated with the necrosis and shedding of the trachea epithelium. Moreover, the ability to replication in the different organs of chickens infected with rH120-S1/YZ as reflected by viral loads at multiple time points was lower than that exhibited in the chickens infected with the rIBYZ strain, which demonstrated that the S1 subunit was not the only determinant of viral tropism that was consistent with results by others [57,61,62], and the significant difference in viral load was related to differences in the viral backbone. However, when comparing the rH120-S1/YZ and rH120 strains which carry the same backbone, it was found that the viral RNA of rH120-S1/YZ in the lungs and kidneys was significantly lower than that of rH120, which may due to the replacement of the IBYZ S1 gene in the recombinant virus, whose structure on the surface contains some degree of changes, which we speculated that may affects the functionality of the S protein of coronaviruses.…”
Section: Discussionsupporting
confidence: 85%
“…The reduction of the viral load at 5 dpi in the group infected with the rIBYZ strain may be associated with the necrosis and shedding of the trachea epithelium. Moreover, the ability to replication in the different organs of chickens infected with rH120-S1/YZ as reflected by viral loads at multiple time points was lower than that exhibited in the chickens infected with the rIBYZ strain, which demonstrated that the S1 subunit was not the only determinant of viral tropism that was consistent with results by others [57,61,62], and the significant difference in viral load was related to differences in the viral backbone. However, when comparing the rH120-S1/YZ and rH120 strains which carry the same backbone, it was found that the viral RNA of rH120-S1/YZ in the lungs and kidneys was significantly lower than that of rH120, which may due to the replacement of the IBYZ S1 gene in the recombinant virus, whose structure on the surface contains some degree of changes, which we speculated that may affects the functionality of the S protein of coronaviruses.…”
Section: Discussionsupporting
confidence: 85%
“…The r value calculated from the cross-neutralization test was less than 50, which implied that strain I0737/17 is not serologically related to 4/91. Contrary to this result, we have previously demonstrated that replacing the three HVRs of the avirulent Beaudette strain of IBV separately or simultaneously with the corresponding regions from a GI-19-lineage nephropathogenic strain by reverse genetics does not produce any changes in the serotype of the Beaudette strain (Shan et al, 2018). These results might suggest that the amino acid sequences of the HVRs were not the only factor accounting for the variations in antigenicity of IBVs.…”
Section: Discussioncontrasting
confidence: 73%
“…Like most CoVs, the remaining one third of the genome of IBV encodes four major structural proteins: the spike (S) glycoprotein, the small envelope (E) protein, the membrane (M) glycoprotein, and the nucleocapsid (N) protein. Generally, the S1 subunit of the S glycoprotein is responsible for attachment of the virion to the host cell membrane by interacting with sialic acid, initiating the infection, while the S2 subunit mediates fusion of the virion and cellular membranes by acting as a class I viral fusion protein [5,6]. Two or three small accessory proteins (genes 3, 4 and 5) that vary in number and sequences among IBV strains are interspersed among the genes coding for the structural proteins.…”
mentioning
confidence: 99%